MANAJEMEN PENGELOLAAN OBAT DI DINAS KESEHATAN KABUPATEN BUTON UTARA - Sumriati Sumriati; La Ode Muhammad Sety; I Putu Sudayasa (NHM PRESS, 2022)
Inefficient drug management causes the level of drug availability to decrease, drug vacancies occur, the number of drugs accumulates as a result of inappropriate drug planning. The purpose of this study was to determine the management of drug management. This research is a type of descriptive research and the data obtained are qualitative data. The informants in this study were 4 informants. The data is processed using triangulation technique and analyzed by Content Analysis. The results of this study show that drug planning at the Health Office of North Buton Regency is based on the Usage Report and Drug Request Sheet (LPLPO) reports that are in accordance with disease patterns and the number of local residents, and must be based on DOEN and Fornas which are carried out every month. Drug procurement at the Health Office of North Buton Regency is carried out using the procurement method through e-purchasing or manually (offline) every 1 year. Procurement is carried out in accordance with the contract agreement with the Distribuor appointed by the Health Office of North Buton Regency. The drug storage used is using the FIFO and FEFO principles, the dosage forms are arranged alphabetically and damaged and expired drugs are separated from suitable drugs. The distribution is carried out in accordance with the plan for drug needs at the Puskesmas. which is divided into 2 types, namely routine distribution and special distribution. However, the problem is related to the distribution of drugs that are still not according to the request of the Puskesmas and there are drugs that are approaching their expiration date. Drug elimination is carried out every 1 year by collecting damaged and expired drugs from the Puskesmas through the Puskesmas report. In carrying out the elimination of drugs, an official report is needed which is signed by the head of the North Buton District Health Office as evidence of the abolition activities by presenting witnesses.